Pengembangan Komik Berbantuan Canva For Education Pada Kelas IV di Sekolah Dasar 101 Bungo - Aldino, Aldino; Mufti, Dhini (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
Education must adapt, one way being by involving technology in the learning process. The delivery of material through images will facilitate the process while helping students to remember and understand it, especially material with a high level of complexity. SDN 101 Bungo still uses the Merdeka curriculum in every fourth grade class. The researcher conducted an initial observation at SDN 101 Bungo on October 20, 2025. The observation focused on IPAS (Science, Social Studies, and Culture) learning in Grade IV on the learning outcome where students analyze the relationship between the form and function of human body parts, namely the five senses (panca indra). The result showed that IPAS learning in that class only utilized textbooks. This study uses a Research and Development (R&D) type of research. The development of a comic media assisted by Canva for Education on the five senses material in Grade IV of elementary school is highly valid, with a final material validation score of 3.95, a final media validation score of 4, and a final language validation score of 4.9. The level of practicality in the small group trial was an average of 4.6, and the large group average was 4.33. Therefore, from the interviews and the results of the questionnaire acquisition, the comic media assisted by Canva for Education on the five senses material in Grade IV of elementary school is concluded to be highly practical and efficient.